Authenticity and Ambivalence: Toward Understanding the Enhancement Debate - Parens, Erik (The Hastings Center report, 2005)
The differences between critics and proponents of enhancement technologies are easily overblown. Both sides of this debate share the moral ideal of being “authentic” to oneself. They differ in how they prefer to understand authenticity, but even this difference is not as stark as it sometimes seems.